Development of a Multi-Perspective Digital Archive Learning Platform with Online Discussions to Enhance Critical Thinking in Generation Z - Muhhamad Mubin Rahmat; Anisya Mukhlisya; Andriani; Muhammad Darwan; Widya Sari Asis; Nurliani Rusli (Jurusan Teknik Informatika dan Komputer, 2024)
This study aims to develop and evaluate a multiperspective learning platform on the G30S/PKI event using digital archives and online discussion forums to enhance critical thinking among Generation Z students. Existing history education often presents a single narrative, limiting students’ ability to analyze historical events critically. This study addresses this gap by providing diverse historical perspectives through an interactive digital platform. A quasi-experimental design with pretest-posttest control groups was employed. Participants consisted of 120 senior high school students selected through stratified random sampling. The platform integrated archival materials, interactive timelines, and moderated discussion forums. Critical thinking was measured using a validated assessment instrument comprising 30 items scored on a 5-point Likert scale, with Cronbach’s alpha of 0.89 indicating high reliability. Data analysis included paired and independent t-tests to compare pre- and post-intervention performance between experimental and control groups. Results revealed a significant increase in critical thinking scores among students using the multiperspective platform (M=83.7, SD=5.4) compared to the control group (M=72.3, SD=6.1), p < 0.001. Students also demonstrated improved digital literacy and engagement in historical discussions, confirming the platform’s effectiveness in fostering analytical skills and reflective learning. The study demonstrates that multiperspective digital platforms can effectively enhance historical reasoning and critical thinking. Limitations include the short intervention duration and focus on a single historical event, which may constrain generalizability. Future research should expand to diverse historical contexts and longitudinal designs. This research provides a novel integration of digital archives and collaborative online discussion to support critical thinking in history education, offering a scalable model for promoting analytical skills and historical empathy among digitally native learners.